Konsepsi Demokrasi Menurut Al-Qur'an - Samsul Bahri; Nurkhalis Nurkhalis; Muhammad Rizki (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2021)
Democracy is one of the power management systems considered the most suitable to be applied in modern countries today. As a source of guidance for humans, the Qur'an has explained the concept of the system of administering power. The conception of democracy is thus believed to be accommodated in the Qur'an. On that basis, the main problem that needs to be answered is, what is the conception of democracy in the Qur'an? The data for this paper was collected by following the steps in the mawḍu'i interpretation, after that, it was analyzed by following the thematic interpretation stage. The results of the analysis show that the term of the Qur'an, which represents the meaning of democracy, is syurā. In suyrā, norms are found that regulate the necessity of conducting deliberation in worldly affairs, both family affairs, muamalah, and political affairs. The concept of democracy in the form of syrā is mentioned in QS. Al-Baqarah: 233, QS. Ali 'Imrān: 159, and QS. al-Syurā: 38. There are four points of connection between the verses of the Qur'an about democracy and democracy today. First, the obligation to hold opinion meetings and prohibit dictators. Second, freedom of expression. Third, respecting opinions that are superior to the results of deliberation. Fourth, the majority vote is taken into account by protecting the rights of minorities. Demokrasi merupakan salah satu sistem pengelolaan kekuasaan yang dipandang paling cocok untuk diterapkan di negara-negara modern dewasa ini. Sebagai sumber petunjuk bagi manusia, Al-Qur’an telah menjelaskan konsepsi mengenai sistem penyelenggaraan kekuasaan. Konsepsi mengenai demokrasi dengan demikian diyakini terakomodasi dalam Al-Qur’an. Atas dasar itu, permasalahan utama yang perlu dicarikan jawabannya adalah, bagaimanakah konsepsi demokrasi dalam Al-Qur’an? Data untuk tulisan ini dikumpulkan dengan mengikuti langkah-langkah dalam tafsir mawḍu’i, selanjutnya dianalisis dengan tahapan penafsiran secara tematik. Hasil analisis menunjukkan bahwa terma Al-Qur’an yang merepresentasikan makna demokrasi adalah syūrā. Dalam syūrā ditemukan norma yang mengatur keharusan melakukan musyawarah dalam urusan-urusan duniawi, baik urusan keluarga, muamalah, maupun urusan bidang politik. Konsep demokrasi dalam bentuk syūrā disebutkan dalam QS. Al-Baqarah: 233, QS. Āli ‘Imrān: 159, dan QS. al-Syūrā: 38. Terdapat empat poin hubungan ayat-ayat Al-Qur’an tentang demokrasi dan demokrasi masa kini. Pertama, kewajiban melakukan temu pendapat dan melarang diktator. Kedua, kebebasan mengeluarkan pendapat. Ketiga, menghargai pendapat yang lebih unggul dari hasil musyawarah. Keempat, suara mayoritas diperhitungkan dengan melindungi hak-hak minoritas.